Determination of acylcarnitines in intact brain tumors using coated blade spray mass spectrometry (CBS-MS) - Joanna Bogusiewicz; Karol Jaroch; Jacek Furtak; Marcin Birski; Krystyna Soszyńska; Anna Majdańska; Agata Ryfa; Marek Harat; Barbara Bojko (Advances in Sample Preparation, 2025)
Potential biomarkers of cancerous alterations could be selected by profiling a wide range of analytes. For this purpose, analytical platforms enabling detailed analysis of different biological matrices are applied. However, after biomarker selection, it is essential to shorten the analysis time as much as possible to speed up the diagnostic process. Therefore, this study aimed to optimize and test the coated blade spray mass spectrometry (CBS-MS) method in analyzing potential biomarkers in brain tumor studies: acylcarnitine. Meningiomas with different mutation statuses in NF2 were studied due to the relation of NF2 mutation with the higher risk of malignant transformation and multiple meningiomas. The application of CBS-MS enabled the determination of acetylcarnitine concentration (AC C2:0) and propionylcarnitine (AC C3:0) in intact tumor tissue. However, it would be necessary to enlarge the study group to confirm the conclusions on the concentration of these analytes in NF2 mutant and wild-type meningiomas. Apart from qualitative analysis, the simultaneous detection of a wide range of acylcarnitines in untargeted analysis was also possible.